2015
DOI: 10.1097/aln.0000000000000467
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Malignant Hyperthermia Diagnoses in Hospital Discharge Records

Abstract: Approximately one quarter of ICD-9 or ICD-10 coded MH diagnoses in hospital discharge records refer to incident MH episodes and an additional 47% to MH susceptibility (including personal history or family history). Information such as surgical procedure, anesthesia billing data, and dantrolene administration may aid in identifying incident MH cases among those with an ICD-9 or ICD-10 coded MH diagnosis in their hospital discharge records.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…However, a general anesthetic may be required after a vaginal delivery in some circumstances such as the removal of a retained placenta or an exploration of the uterine cavity because of a postpartum hemorrhage. Moreover, as indicated in our previous study, most of the MH diagnoses in hospital discharge records refer to positive MH history and susceptibility rather than acute MH episodes [25]. These two factors may explain why the prevalence of MH diagnosis in vaginal delivery was much lower than in cesarean delivery (0.29 per 100,000 versus 0.81 per 100,000.…”
Section: National Inpatientmentioning
confidence: 64%
See 1 more Smart Citation
“…However, a general anesthetic may be required after a vaginal delivery in some circumstances such as the removal of a retained placenta or an exploration of the uterine cavity because of a postpartum hemorrhage. Moreover, as indicated in our previous study, most of the MH diagnoses in hospital discharge records refer to positive MH history and susceptibility rather than acute MH episodes [25]. These two factors may explain why the prevalence of MH diagnosis in vaginal delivery was much lower than in cesarean delivery (0.29 per 100,000 versus 0.81 per 100,000.…”
Section: National Inpatientmentioning
confidence: 64%
“…Second, identification of MH diagnosis relies on the accuracy of coding in discharges data and is susceptible to misclassification because of error or absence of coding. In a previous study evaluating the accuracy of MH diagnosis in hospital discharge records, we found that the ICD-9-CM code 995.86 ("Malignant hyperthermia due to anesthesia") corresponded to a MH crisis in 24% of the cases, to a MH history in 47%, and to fever unrelated to MH in 24% [25]. Therefore, most of the cases with an MH diagnosis identified in the present study should be regarded as MH susceptibility rather than incident MH episodes.…”
Section: National Inpatientmentioning
confidence: 95%
“…There is no test that can be applied acutely to distinguish MH from other causes of hypermetabolism or hyperthermia [4]. The symptoms may occur at any time during the perioperative period and can be highly variable.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of using dantrolene with our patient certainly outweighed the risks, resulting in a favorable outcome, but such prudent clinical decisions may have long-lasting effects. Pinyavat et al explain that miscoding for MH, preemptively treating suspicious cases with dantrolene (as with our case), and even simply having a family member with the disease have contributed to a significant number of cases being added to Medicaid and Medicare databases, as well as individual state hospital discharge databases, listing MH as “present on admission,” and have resulted in MH being identified as a preexisting condition [4]. Without confirmation via the caffeine-halothane contracture test, we will never be certain of the diagnosis with our patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation